A thematic analysis of research on global sourcing and international purchasing in retail firms. Issue 1 (2014) - ,; ,
<x xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to offer a thematic analysis of global sourcing and international purchasing issues in international retail firms. Design/methodology/approach – We review literature that addresses purchasing/sourcing activities of retail firms in foreign markets. We categorize this literature into different themes and analyse how these themes are conceptually or empirically linked to performance. We then use the thematic analysis as a foundation for suggesting potential avenues for future research. Findings – Four distinct themes emerge from our literature review. Originality/value – There is a lack of research that addresses how retail firms can extract value from global sourcing and international purchasing activities. A thematic review, along with a careful classification of different themes, could lead to an enhanced understanding of the processes and objectives that underpin global sourcing and international purchasing activities in retail firms. <ack> <x xml:space="preserve">Acknowledgements</x> The authors gratefully thank Ragnar Söderberg's foundations for financial support. </ack>